Solving engineering optimization problems with the simple constrained particle swarm optimizer - Cagnina, Leticia Cecilia (2008)
This paper introduces a particle swarm optimization algorithm to solve constrained engineering optimization problems. The proposed approach uses a relatively simple method to handle constraints and a different mechanism to update the velocity and position of each particle. The algorithm is validated using four standard engineering design problems reported in the specialized literature and it is compared with respect to algorithms representative of the state-of-the-art in the area. Our results indicate that the proposed scheme is a promising alternative to solve this sort of problems because it obtains good results with a low number of objective functions evaluations.